Aplikasi Perpustakaan Sederhana SMP Karya Pembangunan Ciparay Berbasis Bahasa Pemrograman Website dengan Framework Codeigniter - Geaniva Melandri; Fahmi Abdullah (Melati Institute, 2023)
In the framework of the final project research carried out as one of the requirements before preparing the final project. research is realized in an agency or company that has a function as an application of student learning outcomes in their field of expertise. The intended agency or company is the Ciparay Development Karya Junior High School institution, this research was carried out in approximately one month. For the results given to the object of research is to design and design a simple web-based library application with the help of the codeigniter programming language and the database used is MySQL which will function to the institution. The reason for making this website-based simple library application is that the Karya Pembangunan Junior High School library still uses manual methods in the admin data collection activities in the school library.